Characterization of radiation damage in ceramics: Old challenge new issues?. Issue 9 (13th April 2015) - Simeone, David; Costantini, Jean Marc; Luneville, Laurence; Desgranges, Lionel; Trocellier, Patrick; Garcia, Philippe
Abstract: Abstract : This work is an overview of the physical approaches required for characterizing and understanding the long-term evolution of ceramics under irradiation. Because this subject is complex and has many ramifications, we have chosen to address the problem by looking at the behavior of a number of key ceramics. In the first part of this work, we present the physical mechanisms responsible for the production of primary defects, pointing out the main differences between metals, semiconductors, and insulators. In part two, we attempt to show how devoted experimental techniques can combine with transmission electron microscopy and x-ray techniques to provide a clearer picture of the long-term evolution of the microstructure of ceramics under irradiation. The last part of this work is devoted to discussing different approaches to explain and describe the long-term behavior of irradiated ceramics.